THE EFFECT OF ROLE PLAY METHOD (RPM) ON STUDENTS’ ACHIEMENT IN SPEAKING - PUJIHARIATI . (LP2MTBM MAKARIOZ, 2019)
This study was aimed to find out the effect of using role play method (RPM) on the student’s achievement in speaking. This study was conducted by using an experimental design with two-groups. They were experimental and control groups. The location of the research is SMA Negeri 11 Medan. For efficiency and practicality of the research, 60 students were taken as the sample. The data of this research was collected by administrating a test. There was prepared speaking test through role play. To analyze the data, the writer used t-test. The result of the test shows that to 3.14 was higher than the value of ttable from table at the level significant 0f 0.05 (2.000). In other words, it can be said that t- observed or t0 was higher than ttable at the level of significant of 0.05 (2.002) at df= 58 for two tailed test. It can be concluded that the students’ achievement taught by using role play method (RPM) was higher than taught by memorizing dialogue in speaking.